Personal and perceived peer use and attitudes towards the use of nonmedical prescription stimulants to improve academic performance among university students in seven European countries. (1st November 2016) - Helmer, S.M.; Pischke, C.R.; Van Hal, G.; Vriesacker, B.; Dempsey, R.C.; Akvardar, Y.; Guillen-Grima, F.; Salonna, F.; Stock, C.; Zeeb, H.
Highlights: Students' nonmedical use of prescription stimulants (NMUPS) varied across Europe. Personal approval of NMUPS was high among European university students. Students perceived the peer NMUPS to be higher than their personal use. Perceived peer use was associated with higher personal use of NMUPS. Abstract: Background: Overestimations of non-prescribed stimulant use of peers are well documented in the USA and have also been identified as predictive of personal stimulant consumption. This study aimed to examine whether overestimations of peer use and approval of the use are associated with personal use and attitude towards the use of non-prescribed stimulants among European university students. Method: The EU funded 'Social Norms Intervention for the prevention of Polydrug usE (SNIPE)' study was conducted in seven European countries. In a web-based questionnaire, 4482 students were asked about their personal use and their attitude towards non-prescribed stimulant use, as well as the perceived peer use and peer attitude. Results: 59% of students thought that the majority of their peers used non-prescribed stimulants more frequently than themselves, and only 4% thought that the use of the majority was lower than their personal use. The perception that the majority of peers had used non-prescribed stimulants at least once was significantly associated with higher odds for personal use of non-prescribed stimulants (OR: 3.30, 95% CI: 2.32–4.71). In addition, the perception that the majority of peers approved of the non-prescribed use of stimulants was associated with a 4.03 (95% CI: 3.35–4.84) times higher likelihood for personal approval. Discussion: European university students generally perceived the non-prescribed use of stimulants of peers to be higher than their personal use. This perception, as well as a perception of higher approval in the peer group, was associated with a higher likelihood of personal non-prescribed stimulant medication use and approval.